Effect of Varying Illumination and Temperature on Steady-State and Dynamic Parameters of Dye-Sensitized Solar Cell Using AC Impedance Modeling - Brijesh Tripathi; Pankaj Yadav; Manoj Kumar (International Journal of Photoenergy)
The steady-state current-voltage curve and dynamic response of a dye-sensitized solar cell (DSSC) is mathematically modeled based on electrical equivalent circuit. The effect of temperature and illumination on the steady-state and dynamic parameters of dye-sensitized solar cells is studied. It is found that the dynamic resistance of DSSC decreases from 619.21 Ω to 90.34 Ω with the increase in illumination level from 200 W/m2 to 800 W/m2. A positive temperature coefficient of dynamic resistance is observed. The interfacial charge transfer and recombination losses at the oxide/dye/electrolyte interface are found to be the most influential factor on the overall conversion efficiency and included in the mathematical model. The saturation current of rectifying diode and saturation current of recombination diode are responsible for the transfer recombination losses and have major influence on the overall conversion efficiency.